Structural and Optical Properties of Zinc Doped CdS Thin Films - Karunathi U.; Pabahar S.; Sikanth S.; Karunkaran R.T (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2018)
In this paper, different aspects and facts concerned with the synthesis of thin films of lead chalcogenides along with its opto-electro-structural properties is presented. The polycrystalline thin ﬁlms were put onto chemically clean and optically plane glass substrates by chemical bath deposition technique from aqueous solutions of Cadmium chloride, Zinc acetate, thiourea, triethanolamine and ammonia. X-ray diffraction analysis has been used for the structural characterization. It indicates that the crystallized layers are cubic in form. By using Scherrer’s formula and the data obtained from the XRD studies,the grain size was calculated as 16.5 nm. The band gap energy estimated for Zinc- doped CdS thin films is 2.95 eV.